Aberrant Cerebral Activity in Early Postmenopausal Women: A Resting-State Functional Magnetic Resonance Imaging Study - Zhang, Si; Hu, Junhao; Fan, Weijie; Liu, Bo; Wen, Li; Wang, Guangxian; Gong, Mingfu; Yang, Chunyan; Zhang, Dong (Frontiers in Cellular Neuroscience, 2018)
Background: Early postmenopausal women are frequently associated with cognitive impairments and emotional disorders, such as lack of attention, poor memory, deficits in executive function and depression. However, the underlying mechanisms of these impairments remain unclear. Method: Forty-three early postmenopausal women and 44 age-matched premenopausal controls were involved in serum sex hormone analysis, neuropsychological testing and resting-state functional magnetic resonance imaging (rs-fMRI) data acquisition. Degree centrality (DC) analysis was performed to confirm the peak points of the abnormal functional brain areas as seeds. Subsequently, the functional connectivity (FC) between these abnormal areas and other voxels in the whole brain was calculated. Finally, the sex hormone levels, neuroimaging indices and the neuropsychological data were combined to detect potential correlations. Results: Compared with the premenopausal controls, the early postmenopausal women exhibited significantly higher serum follicle-stimulating hormone (FSH) levels, more severe climacteric and depressive symptoms, worse sleep quality, and more extensive cognitive impairments. Concurrently, the neuroimaging results showed higher DC values in the left amygdala (AMYG.L) and lower DC values in the left middle occipital gyrus (MOG.L). When we used the AMYG.L as the seed point, FC was increased in the left insula (INS.L), bilateral prefrontal cortex (PFC) and right superior frontal gyrus (SFG.R), which are related to a depressive state, worse sleep quality and decreased executive function. When the MOG.L was used as the seed point, the FC in the right middle temporal gyrus (MTG.R) and left inferior parietal gyrus (IPG.L), two areas closely associated with impaired memory, was decreased. Conclusion: These results illuminated the regional- and network-level brain dysfunctions in early postmenopausal women, which might provide information on the underlying mechanisms of the different cognitive impairments and emotion alterations observed in this group.